Konsulat Jenderal Indonesia di Davao dalam Melindungi Hak-Hak Warga Negara Indonesia di Mindanao - Hayanda, Firsta Falah; Azizah, Nur (Jurusan Ilmu Politik Universitas Bangka Belitung, 2024)
In 2016, the Indonesian Consulate General in Davao and UNHCR registered 8,745 Persons of Indonesian Descents (PIDs). Furthermore, 2,399 of them have been confirmed as Indonesian citizens. Since 2020-2023, there have been approximately 30 cases experienced by the Indonesian diaspora in Mindanao such as criminal acts and lack of documents for Indonesian citizens. This research aims to analyze how the Indonesian Consulate General in Davao's efforts to provide legal protection to the Indonesian diaspora in Mindanao. This research uses a qualitative method by collecting secondary data from literature studies such as books, journal articles, websites, reports, and another research. The findings of this study show that the Indonesian Consulate General in Davao in providing assistance on various legal issues, offers legal assistance to Indonesian citizens involved in various criminal and civil cases by providing or arranging the services of lawyers. The Indonesian Consulate General in Davao also cooperates with the Philippine Department of Justice (DOJ), with the assistance of UNHCR Philippines in order to provide legal identity to undocumented Indonesian citizens.